The energy conversion efficiency comparison between ordered and disordered structures in two dimensional semiconductor solar cell: The kinetic Monte Carlo simulation - Supatutkul C. (2017)
© 2016 Taylor & Francis Group, LLC. This study investigated the effect of morphologies between ordered and disordered structures on the internal quantum efficiency (IQE) of organic solar cell in two dimensions using kinetic Monte Carlo simulation. The results showed that the IQE has strong relationship with the morphological parameters such as interface area between P- and N-types, the amount of P- and N-type materials in the domains connected to the electrodes and percolation behavior of the materials across the electrodes. However, the relationship among IQE and the morphology parameters was found rather complicated and even non-linear fit to predict the outcome of IQE from the input parameters does not work well. Therefore, a knowledge based modeling, i.e. Artificial Neural Network (ANN), was used to predict the quantitative behavior of IQE. From the ANN results, the predicted IQE dependent on the morphological parameters agree very well with the targeted results. This therefore proves that the IQE database constructed using ANN is accurate and could be served as the foundation for higher dimension in the future.